Diyat and Local Wisdom: Customary Law-Based Resolution of Assault Conflicts in the Lintang Community - Agustini; Aibdi Rahmat; Jonsi Hunadar (Lembaga Bale Literasi, 2026)
This study examines the relationship between the Qur'anic concept of diyat and the customary law practices of the Lintang community in resolving assault conflicts through a restorative justice perspective. It aims to analyze the conceptual foundations of diyat in the Qur'an and explore how its values are contextualized within local customary law. A qualitative design employing normative and socio-legal approaches was adopted. Primary data were collected through in-depth interviews with village authorities, customary leaders, religious leaders, perpetrators, victims' family members, and community representatives in Muara Karang Village, Empat Lawang Regency, South Sumatra. Secondary data were obtained from the Qur'an, Islamic legal literature, statutory regulations, and relevant scholarly publications. Data were analyzed using a qualitative comparative approach. The findings indicate that the principles of justice (al-'adl), public welfare (maslahah), and forgiveness (al-'afw) embodied in diyat are reflected in the Lintang customary legal system through conflict de-escalation, family mediation, deliberative settlement, medical compensation (biaya beubat), and peace compensation (uang damai). These customary mechanisms not only compensate victims but also restore social relationships, prevent retaliatory violence, and strengthen community harmony. The study concludes that the Lintang customary law represents a contextual implementation of the restorative values of diyat, demonstrating that Islamic legal principles and local wisdom can be effectively integrated into a culturally legitimate and sustainable model of assault conflict resolution. These findings contribute to the development of restorative justice by highlighting the complementary roles of Islamic law and customary law in contemporary conflict resolution.